2002
DOI: 10.1210/jc.2002-020694
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Adiponectin Concentrations in Children: Relationships with Obesity and Insulinemia

Abstract: Adiponectin, a novel adipokine with anti-inflammatory and insulin-sensitizing properties, has been found to have independent negative associations with obesity and hyperinsulinemia/insulin resistance in adults. We measured fasting plasma adiponectin and insulin concentrations and body composition (dual-energy x-ray absorptiometry or doubly labeled water) in 30 5-yr-old (11 boys and 19 girls) and 53 10-yr-old (17 boys and 36 girls) Pima Indian children. A subgroup of 20 children (5 boys and 15 girls) had all me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
174
11
14

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 272 publications
(222 citation statements)
references
References 32 publications
23
174
11
14
Order By: Relevance
“…It has been reported that adiponectin levels are decreased in young and adolescent subjects who are obese [25][26][27][28]. The present results also demonstrated that circulating adiponectin levels were significantly decreased in the obese young women.…”
Section: Discussionsupporting
confidence: 81%
“…It has been reported that adiponectin levels are decreased in young and adolescent subjects who are obese [25][26][27][28]. The present results also demonstrated that circulating adiponectin levels were significantly decreased in the obese young women.…”
Section: Discussionsupporting
confidence: 81%
“…As described previously, obese-susceptible individuals exhibit hypoadiponectinemia, whereas the administration of this hormone in rodents produces an increase in fatty acid oxidation (Fruebis et al, 2001) and helps to lose weight by increasing EE, without affecting food intake (Qi et al, 2004). These observations suggest that the lower %DIT and the difficulty in achieving fat and energy balance observed in susceptible subjects could be related with their hypoadiponectinemia, although several studies have suggested that the drop in adiponectin levels seems to be more likely a consequence than a cause of obesity (Maeda et al, 2002;Stefan et al, 2002). In addition, our data also support previous studies about the role of adiponectin deficiency in the development of insulin resistance (Hotta et al, 2001;Kubota et al, 2002) and cardiovascular risk associated with obesity (Kumada et al, 2003;Pischon et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Nesta, a regressão linear simples mostrou correlação negativa com o escore z de IMC, em concordância com outros estudos 11,12 , mas na regressão linear múltipla a correlação perdeu significância estatística, possivelmente pela presença de confundimento estatístico entre estas variáveis. A dificuldade em elucidar essa questão passa pelo fato de que as relações entre os fatores de risco tradicionais para doenças cardiovasculares e a A correlação positiva da adiponectina com o HDL-colesterol (p = 0,034) na regressão linear múltipla, independente de escore z de IMC, HOMA-IR, leptina, cintura, idade ou sexo, está de acordo com outros estudos que também mostraram que a hipoadiponectinemia está mais fortemente relacionada com dislipidemia que com grau de obesidade 28 .…”
Section: Variáveisunclassified
“…Seus níveis se correlacionam negativamente com obesidade, hiperinsulinismo, resistência à insulina, níveis de triglicérides e LDL-colesterol e, positivamente, com HDL-colesterol 10,11 .…”
Section: Introductionunclassified